Konsep Sikap Keseimbangan dalam Beragama Menurut Al-Qur’an (Analisis Penafsiran Ibnu Katsir terhadap Surah Al-Maidah Ayat 77 dan Al-Hajj Ayat 78 dalam Tafsir Al-Quran Al-Azhim) - Danisha, Danisha (ANWARUL, 2023)
The concept of life balance embodied in the Qur'an is stronger, whole and perfect because God, humans and nature are interconnected, the senses, mind and heart work together, the spiritual and material go hand in hand, individuals and society walk together between the world and the hereafter. mutually useful. Researchers are interested in researching the concept of balance in the perspective of the Qur'an with the aim of knowing how the concept of balance is regulated and described in the holy Qur'an according to the interpretation of ibn katsir. The research uses a library research approach by studying books and research previously relevant to the main points of discussion and problems from the analysis of a reference obtained from the desired data in depth. Al-Qur'an various concepts of balance related to human life and its development in the history of civilization. This concept includes the balance between rights and obligations, law and justice, actions and rewards, the balance of the universe, the relationship with God and humans, to the balance between the life of the world and the hereafter.